Moving (Up) in the World: Displacement, Transformation and Identity in the Grimms’ Fairy Tales - Kujundžić Nada (Croatia, 2025)
The aim of this paper is to examine the significance and functions of displacement in fairy tales published in the final, seventh edition of Jacob and Wilhelm Grimm’s Kinder- und Hausmärchen (Children’s and Household Tales, 1857). I propose that the displacement of the fairy-tale protagonist is a prerequisite for the encounter between the realistic and the marvellous which is one of the distinguishing features of the genre. In addition, the said dislocation necessarily brings about some kind of transformation of the protagonist, usually manifested as material gains and improvement in social standing. Special attention is given to the correspondence between changes in narrative space and changes of the protagonist’s (social) identity.